Ifenprodil tartrate treatment of adolescents with post-traumatic stress disorder: A double-blind, placebo-controlled trial. (May 2022) - Sasaki, Tsuyoshi; Hashimoto, Kenji; Niitsu, Tomihisa; Hosoda, Yutaka; Oda, Yasunori; Shiko, Yuki; Ozawa, Yoshihito; Kawasaki, Yohei; Kanahara, Nobuhisa; Shiina, Akihiro; Hashimoto, Tasuku; Suzuki, Takaaki; et al.
Highlights: This is the first report in treating adolescent PTSD subjects in a randomized, double-blind, placebo‐controlled trial method. Our study suggests that ifenprodil may prove to be a short-term effective alternative safe treatment for adolescent patients with PTSD. Abstract: Background: Several lines of evidence suggest that glutamatergic neurotransmission via the N-methyl-D-aspartate (NMDA) receptor plays a role in certain behavioral manifestations common to Post-Traumatic Stress Disorder (PTSD). Ifenprodil tartrate is a neuroprotective agent that binds to the GluN2B subunit of the NMDA receptor. The aim of this study is to confirm whether ifenprodil tartrate is effective in the adolescent PTSD patients. Methods: This is a randomized, double-blind, placebo‐controlled trial. Ten adolescent (13 to 18 years old) PTSD patients were randomized into two arms: placebo ( n = 4), 40 mg/day ifenprodil tartrate ( n = 6) for 4 weeks. All of the patients were assessed by IES-R-J (Primary outcome measure), TSCC-J, CDRS-R, DSRS-C-J and CGI-I. Results: A comparison of baseline IES-R-J total scores and 4-week end-point scores showed a mild trend of improvement ( p = 0.0895) and the difference score was -9.314. A comparison of baseline scores and 2-week intermediate-point scores showed that IES-R-J hyperarousal subscores and TSCC-J subscores (dissociation subscores, sexual concerns subscores) improved significantly. A comparison of baseline TSCC-J sexual concerns subscores and 4-week end-point scores improved significantly. Conclusions: Our study may prove to be an short-term effective alternative safe treatment for adolescent patients with PTSD.